MINERALOGICAL DIFFERENCES BETWEEN ANCIENT SHERDS AND EXPERIMENTAL CERAMICS: INDICES FOR FIRING CONDITIONS AND POST- BURIAL ALTERATION - Rathossi, C.; Pontikes, Y.; Tsolis-Katagas, P. (Bulletin of the Geological Society of Greece, 2010)
Results are reported regarding laboratory-scale experimental work aiming to reproduce ceramic specimens with macro and micro characteristics similar to ancient sherds. Small differences in mineralogical composition between ancient sherds and experimental ceramics elucidated the effect of the firing conditions and the degree of post-burial alteration of ancient ceramics. Scarsity of gehlenite (Ca2Al2SiO7) in sherds for which firing temperature has been estimated between 800 to 950°C, led to higher Fs/Gh (fassaite/gehlenite) ratio in respect to that recorded for the ceramic specimens. This fact is attributed to the dissolution of gehlenite during the post-burial alteration, the ancient ceramics were subjected to, but also due to the short sintering duration (i.e. higher heating rate and/or low soaking time) applied by the potters in some cases.